Effects of natural-gas blending on ignition delay and pollutant emission of diesel fuel for the condition of homogenous charge compression ignition engine. (15th November 2022) - Han, Hee Sun; Han, Ka Ram; Wang, Yuangang; Kim, Chul Jin; Sohn, Chae Hoon; Nam, Chungwoo
Highlights: Effects of blending of natural gas (NG) with diesel fuel were investigated. Major properties of diesel were measured at 40 bar and its surrogate fuel was formulated. Blending of NG reduces pollutant emission with slight decrease in heat production. Ignition timing is changed by NG blending, but, it is not significant. The optimal mixture ratio of NG in the dual fuel is suggested in HCCI engines. Abstract: Burning of dual fuel of diesel and natural gas is a promising technique in compression ignition engine in the aspects of fuel economy and reduced emission. Effects of blending of natural gas with diesel fuel are investigated numerically and experimentally with respect to ignition delay, heat production, and pollutant emission. First, major properties of diesel are measured at high pressure of 40 bar, which is an engine-relevant condition, and thereby, a surrogate fuel with higher accuracy is formulated, which has properties closer to diesel than the other existing surrogate fuels. Especially, as one of key properties, high molecular weight of diesel is considered critically in formulating a surrogate fuel. Ignition delay times of several mixtures of diesel and natural gas (NG), of which mixture ratios of 100/0%, 60/40%, and 20/80%, are measured by a shock tube in the ranges of temperature from 770 K to 1, 000 K and of equivalence ratios from 0.5 to 2.0. Measured ignition delay is compared with that calculated by numerical simulations with the surrogate fuel formulated in this study for its validation. Finally, combustion simulations of HCCI (homogeneous charge compression ignition) are conducted with the mixture of diesel and NG and compared with available experimental data. And thereby, optimal mixture ratio of the dual fuel is suggested in terms of ignition time and pollutant emission acceptable in HCCI engines.